(untitled) (Research, Society and Development, 2020)
The Education through Work for Health Program (PET-Saúde) is an initiative of the Ministry of Health to qualify professionals and train students in the health field. In 2018, PET-Saúde had as its theme Interprofessionality. This descriptive essay, of the experience report type, aims to describe the aspects that enhance and hinder the actions developed by a tutorial group from PET, considering the dimensions of interprofessional work and collaborative practice. The actions were registered by PET participants in a Google forms form and systematized in July and August 2020 for analysis and discussion. About the aspects that enhance the macro level, the PET-Saúde Project brings up the discussion on interprofessionality involving teaching-service, through the monitors, tutors and preceptors of the health service. In the meso dimension, the contribution to the training of future professionals from an interprofessional perspective and the micro integration of participants from specific areas expressing values, knowledge, behavior and integration of professions. Among the aspects that hinder the actions, the format of the Pedagogical Projects of the courses involved stands out in the macro dimension with little or no emphasis on Interprofessionality. At the meso, it is important to note the little institutional flexibility in the participation of integrated curricular activities. And at the micro level, the lack of articulation between the activities of the Supervised Internship in Health courses in the fields of practice. This essay brought important reflections to the group that point to strategies to consolidate interprofessionality in the midst of health education and work.